Prognostic role of lymph node regression in patients with esophageal cancer undergoing neoadjuvant therapy - Pingrun Chen; Maojia Chen; Yijie Bu; Guowei Che; Chao Cheng; Yan Wang (Frontiers Media S.A., 2024)
PurposeTo clarify the prognostic value of lymph node regression (LNR) status including the lymph node regression grade (LNRG) and N downstaging in patients with esophageal cancer receiving neoadjuvant therapy based on available evidence.MethodsSeveral databases were searched up to 25 March 2024. The main outcomes included overall survival (OS), disease-free survival (DFS) and cancer-specific survival (CSS). Hazard ratios (HRs) and 95% confidence intervals (CIs) were combined. Subgroup analyses based on the neoadjuvant therapy and pathological type were also conducted.ResultsIn total, 14 retrospective studies with 3,212 participants were included. Nine and five studies explored the relationship between LNRG and N downstaging and survival, respectively. Pooled results indicated that complete LNR predicted significantly improved OS (HR = 0.47, 95% CI: 0.41-0.55, P < 0.001) and DFS (HR = 0.42, 95% CI: 0.32-0.55, P < 0.001) and subgroup analysis based on neoadjuvant therapy and pathological type manifested similar results. Besides, N downstaging was also significantly related to improved OS (HR = 0.40, 95% CI: 0.21-0.77, P = 0.006) and CSS (HR = 0.27, 95% CI: 0.12-0.60, P < 0.001).ConclusionLNR could serve as a novel and reliable prognostic factor in patients with esophageal cancer receiving neoadjuvant therapy and complete LNR and N downstaging predict better survival.